Hedge fund investment in ETFs - Douglas J. Cumming; Pedro Monteiro (Goethe University Frankfurt, Center for Financial Studies (CFS), 2023)
This paper examines the causes and consequences of hedge fund investments in exchange traded funds (ETFs) using U.S. data from 1998 to 2018. The data indicate that transient hedge funds and quasi-indexer hedge funds are substantially more likely to invest in ETFs. Unexpected hedge fund inflows cause a rise in ETF investments, and the economic significance of unexpected flow is more than twice as large for transient than quasi-indexer hedge funds. ETF investment is in general associated with lower hedge fund performance. But when ETF investment is accompanied by an increase in total flow and unexpected flow, the negative impact of ETF holdings on performance is mitigated. The data are consistent with the view that hedge fund ETF investment unrelated to unexpected flow is an agency cost of delegated portfolio management.
urn:nbn:de:hebis:30:3-689869
Keywords: G23; 330; Hedge funds; Exchange traded funds; ETFs; Agency costs; Active investors; Delegated portfolio management